Wojna a natura ludzka. Rozważania Zygmunta Freuda - Citkowska-Kimla, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The present analysis is based on the assumption that there is aclose link between an anthropological vision and political views. The main objective is to provide an exegesis of Sigmund Freud’s views on war in the history of civilisation with regard to his vision of human nature. The fundamental element in the author’s reconstruction of Freud’s thought is the essay Civilisation and Its Discontents. In it Freud demonstrates the inevitability of war, which has its permanent source in human nature, more specifically, in the Thanatos drive — drive of death, aggression and destruction.Influenced by his critics e.g. Albert Einstein and Erich Fromm, Freud tried to modify his position on this matter in another essay entitled Why War? The present author’s conclusion is that Freud’s views contradict the anthropological assumptions formulated earlier.
Keywords: Freud, Sigmund (1856-1939); wojna; antropologia; natura ludzka; instynkt życia Eros; popęd śmierci Thanatos; kultura